(untitled) (Conference Zone, 2021)
The XXI century - the century of informatization - has made adjustments to the traditional teaching of foreign languages. To increase the effectiveness of teaching, many teachers introduce information technologies into the educational process (this is the generalized name of technologies responsible for storing, transmitting, processing, protecting and reproducing information using computers) [1]. The problem of using computer technologies is relevant today and is dictated primarily by pedagogical needs to increase the effectiveness of developing learning. Teachers use them to implement research and creative to develop the skills of independent learning activities and the promotion of a new culture. The use of new technologies in teaching a foreign language is due not only to the desire for novelty, but also to a personality-oriented approach to education and upbringing